Identity Crisis in the Female Protagonists of Toni Morrison and Anita Desai: Exploring the Oppression and Rebellion of Female Protagonists in Toni Morrison and Anita Desai's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The study of two contemporary women novelists Toni Morrison and Anita Desai is of immense importance. Although they belong to two different continents and with different socio-cultural background, they share the female space in two ways first because they are women writers and secondly because they write about women. The factors and circumstances which moulded their feminine sensibility are quite different but the female protagonists of both are oppressed ,losing their identity due to social and cultural turmoil and finally rebelling against the accepted norms in search of their own identity.